A new species of Protandrena Cockerell from Brazil (Hymenoptera, Apidae, Andreninae)* - Ramos, Kelli S.; Melo, Gabriel A.r. (Zootaxa, 2006)
Protandrena avulsa new species, from Espirito Santo and Minas Gerais (southeastern Brazil) is described and illustrated. This species is unique within Protandrena for its well-developed pronotal lamella, similar to what is found in Pseudopanurgus and Parapsaenythia, and by its protuberant interantennal area. This is the first record of this bee genus in Brazil.